Caracterização, avaliação e classificação dos pulverizadores autopropelidos produzidos no Brasil - Casali, André Luis (2015)
Brazil is considered the largest consumer of pesticides in the world. To apply these inputs are used, in many cases, hydraulic self-propelled sprayer boom. In Brazil there are few tools that assist the farmer in choosing the ideal model of self-propelled sprayer, optimizing purchasing and reducing costs. Considering the lack of evaluative material from these machines, the central objective of this thesis is to establish a classification system for self-propelled sprayers sold in Brazil, from its theoretical operating capacity and also perform evaluations of some of these specific machine systems. For that, a classification system based on the combined theoretical operational capacity was created, as were tests conducted as the sound pressure inside the cabin of machines in operation and was also evaluated the preview percentage boom. For it was developed an equipment (View Simulator Operator) that simulates an operator sitting in the spray seat. We identified six different types of sprays configuration sold in Brazil, these six types differ as to the boom position, cabin, spray tank and engine. If one can assign advantages and disadvantages to each type of configuration. Considering the 14 brands operating in the Brazilian market and adding models each offers are available 42 models of self-propelled sprayers designed for use in Brazil grain crops. By applying the rating system created in this thesis, the models of self-propelled sprayers manufactured in Brazil were divided into four classes (I, II, III and IV). With increasing class tended to increase the clearance of sprayers, as well as increasing the size of the boom, operation speed and the size of the spray tank, however these items when evaluated independently do not justify the step increase. Regarding the measured sound pressure in the cabin of sprayers with different engine positions, significant differences were observed between the assessed machines, with lower sound pressure on machines with rear engine. As for the percentage of viewing the boom, the machine with the highest visibility has in its central cabin configuration and back boom.